2011
DOI: 10.1177/875687051103000302
|View full text |Cite
|
Sign up to set email alerts
|

Improving Schools through a Response to Intervention Approach: A Cross-Case Analysis of Three Rural Schools

Abstract: While the basic tenets of the RtI model are well-established in the literature, few studies have been conducted to describe its implementation in rural schools. We conducted a qualitative study in three rural schools that had been designated as pilot sites by our state department of education. A cross-case analysis of the data collected through interviews, observations, and document reviews indicated positive changes, including (a) increased use of databased decision-making, (b) increased collaboration among g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…To foreground the purpose of the study for survey, interview, and generational narrative participants, document analysis of CCSS-aligned curriculum documents developed by the teachers in the district was conducted. Just as other researchers have used the review of policy and school documents for the purpose of triangulating interview data (Pashiardis, Savvides, Lytra, & Angelidou, 2011; Shepherd & Salembier, 2011), this study included document analysis to determine whether or not local rural and nonrural cultures had been included in local curricula and, if not, where space may exist for their inclusion. Having been granted access to a shared drive where all of the teacher-developed, CCSS-aligned curriculum-mapping documents were stored, curriculum documents were analyzed through line-by-line coding of the documents ( n = 185 unique codes), followed by thematic organization of like codes using a Microsoft Excel spreadsheet ( n = 3 themes and 9 subthemes), in order to identify the presence or lack of cultural relevancy (i.e., the places in the curricula where local rural and/or nonrural cultures were included or could be included).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To foreground the purpose of the study for survey, interview, and generational narrative participants, document analysis of CCSS-aligned curriculum documents developed by the teachers in the district was conducted. Just as other researchers have used the review of policy and school documents for the purpose of triangulating interview data (Pashiardis, Savvides, Lytra, & Angelidou, 2011; Shepherd & Salembier, 2011), this study included document analysis to determine whether or not local rural and nonrural cultures had been included in local curricula and, if not, where space may exist for their inclusion. Having been granted access to a shared drive where all of the teacher-developed, CCSS-aligned curriculum-mapping documents were stored, curriculum documents were analyzed through line-by-line coding of the documents ( n = 185 unique codes), followed by thematic organization of like codes using a Microsoft Excel spreadsheet ( n = 3 themes and 9 subthemes), in order to identify the presence or lack of cultural relevancy (i.e., the places in the curricula where local rural and/or nonrural cultures were included or could be included).…”
Section: Methodsmentioning
confidence: 99%
“…Based on a review of qualitative studies recommending 10 long interviews with between 6 and 12 participants as ideal for determination of metathemes (Creswell, 1998; Guest, Bunce, & Johnson, 2006), approximately 10 long interviews, lasting 60 to 90 minutes each, with participants ( n = 8) recruited from the pilot study were used to gather enough information about recurring themes while preventing saturation. Like Shepherd and Salembier (2011), who used a semistructured interview protocol of 15 to 18 questions with a variety of educational stakeholders in their study on rural education, this study included 9 to 14 questions (some with multiple parts), depending on the stakeholder interviewed and the level of elaboration provided. Consistent with descriptive phenomenological methodology, follow-up questions were only asked when necessary to clarify participants’ responses and to encourage as complete a description of their experiences as possible, while preventing the influencing of their responses (Englander, 2012; Giorgi, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Robinson et al (2013) found that rural teachers had difficulty implementing the problem-solving component of RTI, presumably as a result of their insufficient experience with and knowledge about the practice and the time-consuming nature of the problem-solving process. Rural schools’ limited access to effective professional development (PD), instructional and financial resources, and specialized staff make it imperative for the different professionals involved in the implementation of RTI to expand their roles to include additional responsibilities associated with the RTI process and develop a common focus and knowledge base (Shepherd & Salembier, 2011).…”
Section: Rti In Rural Schoolsmentioning
confidence: 99%